PEMANFAATAN DAN BIOAKTIVITAS SIDAGURI (Sida rhombifolia) - Marina Silalahi (UNIVERSITAS PGRI MADIUN, 2020)
Sida Rhombifolia is one of the species in the Malvaceae family that is widely used as a medicine including the local Indonesian community. This plant is easily found in various fields such as roadsides, yards, gardens and berra land. This study aims to explain the relationship between SR utilization and bioactivity so that it can be used as a source of information in its development. The method used is a literature review in various books and scientific articles that are published online and offline using the keywords Sida Rhombifolia and the bioactivity of S. Rhombifolia. In ethnobotany SR used as traditional medicine include gout, broken bones, wounds, fever, treatment of diarrhea, malaria, gastrointestinal dysentery, fever, asthma, and inflammation and anti-inflammation. SR has bioactivity as an anti-inflammatory, anti-microbial, antioxidant, anti-cancer, drug for kidney disorders, hepatoprotective, anti-diabetes mellitus, and analgesics. The content of tannins, polyphenols, alkaloids, glycosides, flavonoids and saponins found in SR are related to their bioactivity. Utilization of SR as an anti-microbial especially the Enterobacter digestive tract, kidney disorders and anti-cancer can be developed so that it is used as a new alternative source.